Antidepressant Paroxetine Exerts Developmental Neurotoxicity in an iPSC-Derived 3D Human Brain Model - Zhong, Xiali; Harris, Georgina; Smirnova, Lena; Zufferey, Valentin; Sá, Rita de Cássia da Silveira e; Baldino Russo, Fabiele; Baleeiro Beltrao Braga, Patricia Cristina; Chesnut, Megan; Zurich, Marie-Gabrielle; Hogberg, Helena T.; Hartung, Thomas; Pamies, David (Frontiers in Cellular Neuroscience, 2020)
Selective serotonin reuptake inhibitors (SSRIs) are frequently used to treat depression during pregnancy. Various concerns have been raised about the possible effects of these drugs on fetal development. Current developmental neurotoxicity (DNT) testing conducted in rodents is expensive, time-consuming, and does not necessarily represent human pathophysiology. A human, in vitro testing battery to cover key events of brain development could potentially overcome these challenges. In this study, we assess the developmental neurotoxicity of paroxetine– a widely used SSRI which has shown contradictory evidence regarding effects on human brain development –using a versatile, organotypic human induced pluripotent stem cell (iPSC)-derived brain model (BrainSpheres). At therapeutic blood concentrations, which lie between 20 and 60 ng/ml, Paroxetine led to an 80% decrease in the expression of synaptic markers, a 60% decrease in neurite outgrowth and a 40-75% decrease in the overall oligodendrocyte cell population, compared to controls. These results were consistently shown in two different iPSC lines and indicate that relevant therapeutic concentrations of Paroxetine induce brain cell development abnormalities which could lead to adverse effects.